2003
DOI: 10.1097/00000542-200309000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing Factor Mediates the Antinociceptive Action of Nitrous Oxide in Rats

Abstract: Nitrous oxide activates the CRF system in the brain, which results in stimulation of noradrenergic neurons in the locus ceruleus and its consequent antinociceptive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…However, the mechanisms by which this peptide acts are still unclear [22]. Previous studies have suggested that the analgesic effect of CRF on somatic pain sensitivity may be mediated by both opioid and non-opioid mechanisms [23,24]. For example, a previous report [25] demonstrated that CRF administered i.c.v in anesthetized rats has an analgesic effect on sensitivity to somatic pain (caused by electrical current).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms by which this peptide acts are still unclear [22]. Previous studies have suggested that the analgesic effect of CRF on somatic pain sensitivity may be mediated by both opioid and non-opioid mechanisms [23,24]. For example, a previous report [25] demonstrated that CRF administered i.c.v in anesthetized rats has an analgesic effect on sensitivity to somatic pain (caused by electrical current).…”
Section: Discussionmentioning
confidence: 99%
“…While nitrous oxide is often used for pain relief in normal vaginal delivery and dental procedures, during surgery it is combined with anaesthetic agents. It has been reported in experimental animal studies that the supraspinal opioid receptors are activated through the corticotropine releasing factor of N 2 O [13]. Thus, an interaction occurs between N 2 O and exogenous opioids.…”
Section: Discussionmentioning
confidence: 99%
“…27 Increased corticotropin-releasing hormone production has also been described in the mechanism of nitrous oxide's antinociceptive action. 28 Nitrous oxide, however, is also a noncompetitive inhibitor of the N-methyl-D-aspartate (NMDA) subtype of glutamate receptors 29 and has the capability to activate 2-pore-domain potassium channels, which when activated, hyperpolarize neurons away from their firing threshold. 30 These actions may account for reported neuroprotective effects of nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%